(untitled) (Malay Literature, 2022)
This paper intends to investigate the issue of knowledge and ways of acquiring that knowledge as it is seen in the writings of Malay scholars in Jawi. Malay scholars chosen here are those who have written on this issue via their many writings. Malay writings on Islam are known simply as kitab, denoting their Islamic heritage and background. Within this kitab genre there exist writings on theology (aqidah), jurisprudence (fiqah), and Sufism (tasawwuf) amongst others. For the sake of this paper, this study is limited to the texts mainly in theology. The aim here is to study issues connected to knowledge to come to the epistemology of Malay thinkers. It is presumptuous to think that Malay thinkers are uniform in their thinking and monolithic in their interpretation of religion. The facts speak for themselves that Malay thinkers comprised of a mixed bunch with many from different backgrounds and teachers, thus making one unified epistemology difficult, if not impossible. This research include those texts which are still being published and read by many around the country and in many instances are influential in the formation of the Malay Muslim mindset. The formation of concepts within the mind and thus making a particular view on Islam had begun with the teaching of these primary texts. Perhaps with the study of this aspect of Islamisation, people would be better equipped to understand the Malay Muslim mind of today.